Effects of training on employee suggestions and promotions in an internal labor market - Christian Pfeifer; Simon Janssen; Philip Yang; Uschi Backes-Gellner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
We evaluate the effects of employer-provided formal training on employee suggestions for productivity improvements and on promotions among male blue-collar workers. More than twenty years of personnel data of four entry cohorts in a German company allow us to address issues such as unobserved heterogeneity and the length of potential training effects. Our main finding is that workers have larger probabilities to make suggestions and to be promoted after they have received formal training. The effect on suggestions is however only short term. Promotion probabilities are largest directly after training but also seem to be affected in the long term.
Keywords: J24; M53; 330; Human capital; Insider econometrics; Productivity; Promotions; Training; Betriebliches Bildungsmanagement; Personalentwicklung; Wirkungsanalyse; Vorschlagswesen; Produktivität; Erwerbsverlauf; Deutschland